Development of an Objective Structured Clinical Examination Using the American Board of Anesthesiology Content Outline for the Objective Structured Clinical Examination Component of the APPLIED Certification Examination. Issue 7 (1st October 2018) - Tanaka, Pedro; Adriano, Aileen; Ngai, Lynn; Park, Yoon Soo; Marty, Adrian; Wakatsuki, Shin; Brun, Carlos; Harrison, Kyle; Bushell, Erin; Thomsen, Jakob Louis Demant; Wen, Louise; Painter, Christopher; et al.
Abstract : The goal of this study was to use the American Board of Anesthesiology Objective Structured Clinical Examination (OSCE) content outline as a blueprint to develop and administer a 9-station mock OSCE with station-specific checklists to senior residents (n = 14). The G- and Ф-coefficient reliability estimates were 0.76 and 0.61, respectively. Residents judged the scenarios as either extremely or somewhat realistic (88%). It is feasible to develop and administer a mock OSCE with rigorous psychometric characteristics. Abstract : Supplemental Digital Content is available in the text.